Longitudinal follow-up and outcome analysis in patching resistant/patching noncompliant amblyopic subjects treated with dichoptic amblyopia training - Prasad B Walimbe; Parikshit M Gogate; Tejaswini P Walimbe; Girija M Khaladkar (Journal of Clinical Ophthalmology and Research)
Purpose: The purpose of the study was to estimate the efficacy of dichoptic amblyopia training (DAT) in patching resistant/patching noncompliant amblyopic subjects on best-corrected distance visual acuity and stereoacuity with 12-month follow-up. Methodology: In this study, 113 participants with anisometropic, isometropic, strabismic, and accommodative esotropia with amblyopia, with a mean age of 8 years (interquartile range [IQR] 7–10), using full-time spectacle correction and not improving with prescribed patching protocol in 2 subsequent visits 3 months apart were included in the study. Subjects with deprivational amblyopia, ocular comorbidity, or neuronal defects were excluded. Subjects were given 30 min of dichoptic gameplay with Bynocs DAT for 5 days a week for at least 6 weeks. Best-corrected distance visual acuity and stereoacuity of subjects were recorded before treatment, immediately after Bynocs DAT, 6 months, and at 12-month follow-up. Results: The age group of the participants was divided into three groups – (1) <9 years (64.6%), (2) 10–17 years (33.6%), and (3) >18 years (1.8%). The median (IQR) age of 113 participants was 8 years (7–10). The diagnosis of the participants was anisometropic amblyopia in 18 (15.9%), isometropic amblyopia in 72 (63.7%), accommodative esotropia with amblyopia in 18 (15.9%), and strabismic amblyopia in 5 (4.4%). Post dichoptic therapy, the best-corrected distance visual acuity improvement was statistically significant using the McNemar test and remained stable till the 12-month follow-up (P < 0.001). Post Bynocs DAT, stereoacuity improvement was statistically significant using the McNemar test and maintained till the 12-month follow-up (P < 0.001). Conclusion: Best-corrected distance visual acuity and stereoacuity improved after Bynocs DAT and remained stable in patching resistant/patching noncompliant subjects with anisometropic and isometropic amblyopia 12 months after cessation of treatment.